2014
DOI: 10.1159/000360804
|View full text |Cite
|
Sign up to set email alerts
|

Different Cerebral Responses to Puncturing at ST36 among Patients with Functional Dyspepsia and Healthy Subjects

Abstract: Background: Little research has been done on the connection between functional status and acupuncture efficacy; however, functional status is a key factor in the study of acupuncture efficacy. Therefore, we have tried to compare functional dyspepsia (FD) patients with healthy subjects (HS) to determine the different cerebral responses elicited by acupuncture stimulation at Zusanli (ST36). Patients and Methods: In this study, 24 FD patients and 24 HS were given acupuncture stimulation at ST36 while being monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…All articles [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] were published between 2007 and October 2015 (Table 1). We distinguished two research groups (Group 1: Studies 1, 3, 4; Group 2: Studies 2, 5-16), on the basis of authors and affiliations.…”
Section: Study Selection and Descriptionmentioning
confidence: 99%
“…All articles [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] were published between 2007 and October 2015 (Table 1). We distinguished two research groups (Group 1: Studies 1, 3, 4; Group 2: Studies 2, 5-16), on the basis of authors and affiliations.…”
Section: Study Selection and Descriptionmentioning
confidence: 99%
“…Moreover, studies performed on individuals with FD [24], IBS [51], functional diarrhea [25], Crohn’s disease [52], and healthy controls [53] have found that having influence on the brain activity might be an important reason for modulating effects of acupuncture on gastrointestinal function. For example, our previous study [54] demonstrated that puncturing at ST36 could evoke homeostatic afferent processing network of FD patients, which was confirmed as a pivotal network of acupuncture treating for FD in another study [24]. Therefore, we hypothesize that acupuncture could treat FC through normalizing the pathological alteration of the brain activity.…”
Section: Discussionmentioning
confidence: 68%
“…In this way, it improves the symptoms of FD, with an effective rate of up to 97%. (2) Imaging mechanism: One RCT showed that compared to healthy subjects, acupuncture stimulation at ST36 with fMRI technique evoked pronounced changes in the homeostatic afferent processing network of FD patients [87]. Fang et al [88] found that acupuncture relieved gastrointestinal symptoms and signs using resting-state fMRI, which may be due to the normalization of brain-gut axis in FD patients.…”
Section: Discussionmentioning
confidence: 99%